Extended Cranial Ultrasound Views in Infants with Acute Brain Stem/Infratentorial Lesions: Diagnosis of a Progressive Midline Glioma in a 6-Week-Old Infant - Lange, Matthias; Mitzlaff, Bernd; Beske, Florian; Koester, Holger; Aumann, Wiebke; Woitzik, Johannes; Mueller, Hermann L.; Heep, Axel (Journal of Child Science, 2021)
Central nervous system (CNS) tumors are the most common solid tumors in children and adolescents. However, in neonates and children aged younger than a year, they are very rare. Clinical presentation in neonates is often subtle and nonspecific. When neurological symptoms are apparent at this age, cranial ultrasound (CUS) is often done as the initial evaluation, with a standard approach through the anterior fontanel (AF), followed by further imaging, such as magnetic resonance imaging (MRI), if necessary. We report the first neonatal case of a rapidly progressive diffuse midline glioma positive for histone H3 K27M mutation (World Health Organization [WHO] grade IV) in which using extended (transmastoid) CUS studies through the mastoid fontanelle (MF) in the second month of life defined the lesion in the brainstem.
Keywords: cranial ultrasound; fontanella mastoidea; brainstem glioma